A survey to ascertain peer support models available in Head and Neck cancer across the United Kingdom. Issue 4 (May 2022) - Hatton, R.A.; Crane, J.; Patterson, J.; Rogers, S.N.
Abstract: In cancers and chronic conditions, peer support (PS) has been shown to improve quality of life (QOL) and provide an important coping mechanism for patients, however there is little evidence for this intervention in Head and Neck cancer (HNC). Peer support allows individuals to come together and share information, encouragement, and experiences. It is delivered in a variety of ways including one-to-one, online, and support groups. There is limited literature regarding the timing, barriers, and types of PS available for individuals with HNC across the United Kingdom (UK). The aim of this project was to survey healthcare professionals with respect to their experience regarding types, timings, and barriers to PS in HNC. The survey was developed based on the literature, feedback and advice from a HNC patient research group and healthcare professionals. It was conducted online and consisted of twelve questions. Eighty-eight individuals responded covering twenty-four of twenty-six cancer alliances across the UK. Three main themes with subthemes were identified: patient barriers (emotional barriers and patient limitations), organisational barriers (administrative problems, limited time and resources and COVID-19), and staff barriers (lack of departmental support, concerns with PS and matching and timing of support). The survey demonstrated the different types of PS available across the UK and the barriers faced when implementing this support. It highlighted the complexity of being able to satisfactorily deliver appropriate and effective PS in HNC and the challenges involved.